A pessoa idosa no sistema penitenci??rio: criminalidade, cidadania e condi????es - Magalh??es, Jaira da Silva (2017)
The penitentiary system, over time, underwent several transformations. It was from the concept of a space of punishment only from the State against the one that committed crimes to the search for alternatives of more humanized sentences, through the precepts and dispositions that regulated the Federal Constitution 1988 and all the juridical order that also regulates the prisons institutions. A new fact about which we need to shed light is the growing number of elderly prisoners in prisons for diversified crimes, experiencing the natural process of aging in prison. Therefore, a study was carried out on the elderly in the penitentiary system, developing the relationship between crime, citizenship and the conditions of elderly prisoners. Thus, the question also arises in the investigation of the perceptive aspects of aging in prison, constructing a narrative in the context of a semi-structured interview with a woman and sixteen elderly men, serving a prison sentence in prisons in the Federal District. For that, the methodological triangulation was applied, using techniques of quantitative and qualitative procedures of descriptive, exploratory and reflexive nature. The results revealed that the penitentiary system does not consider the peculiarities arising from the aging process, in terms of deprivation of liberty, such as medical necessity, care, physical facilities, among others. Finally, the aim is to contribute to studies on the elderly by providing elements for planning specific actions and programs for this population, including adapting the prison system to elderly prisoners.